Pro-Environmental Behavior in The Tiga Rasa Rejenu Water Tourism Area - Sodiq, Alwi Mahardhika; Widjanarko, Mochamad (Universitas Al Azhar Indonesia, 2024)
Pro-environmental behavior is a form of human effort that aims to minimize negative impacts on the environment and improve environmental conditions. The Tiga Rasa Rejenu Water Tourism Area is a beautiful place, and it is never empty of visitors from various regions. As a tourist area, pro-environmental behavior should be implemented by the community in order to protect the surrounding environment and the comfort of tourists. This research aims to look at aspects of community pro-environmental behavior in the Tiga Rasa Rejenu Water Tourism Area. This research uses a qualitative descriptive method with a phenomenological approach. The instruments applied in this research used observation and interviews with coding and triangulation data analysis. The subjects in this research consisted of three people, starting from managers, traders and motorcycle taxi workers. The results of this research are that the informant's awareness of pro-environmental behavior has actually been implemented and socialized by the management of the Sheikh Sadzali Rejenu Tomb Foundation, such as saving electricity, mobility and transportation by making special regulations. However, it is still a problem and it is still difficult for people to implement, especially regarding conservation in preserving the environment.Keywords – Air Tiga Rasa, Pro-environmental Behavior, Tourism